Catenation and Aggregation of Multi‐Cavity Coordination Cages. Issue 41 (26th July 2018) - Zhu, Rongmei; Regeni, Irene; Holstein, Julian J.; Dittrich, Birger; Simon, Miriam; Prévost, Sylvain; Gradzielski, Michael; Clever, Guido H.
Abstract: A series of metal‐mediated cages, having multiple cavities, was synthesized from Pd II cations and tris‐ or tetrakis‐monodentate bridging ligands and characterized by NMR spectroscopy, mass spectrometry, and X‐ray methods. The peanut‐shaped [Pd3 L 1 4 ] cage deriving from the tris‐monodentate ligand L 1 could be quantitatively converted into its interpenetrated [5Cl@Pd6 L 1 8 ] dimer featuring a linear {[Pd‐Cl‐]5 Pd} stack as an unprecedented structural motif upon addition of chloride anions. Small‐angle neutron scattering (SANS) experiments showed that the cigar‐shaped assembly with a length of 3.7 nm aggregates into mono‐layered discs of 14 nm diameter via solvophobic interactions between the hexyl sidechains. The hepta‐cationic [5Cl@Pd6 L 1 8 ] cage was found to interact with polyanionic oligonucleotide double‐strands under dissolution of the aggregates in water, rendering the compound class interesting for applications based on non‐covalent DNA binding. Abstract : Catenanes going nuts : A tris‐monodentate ligand assembles with Pd II cations to a peanut‐shaped cage, followed by quantitative catenation to give a five‐cavity inclusion compound. The alkyl‐chain decorated, 3.7 nm long object was further found to aggregate to 14 nm wide discs that can be broken up and solubilized in water by offering polyanionic DNA as interaction partner.